Factors Affecting the Intention to Adopt Mobile Banking. A Study in Klang Valley, Malaysia - Wong, Si’Jie (2013)
This study aims to investigate the factors that affect the intention to adopt mobile banking in Klang Valley through the integration of the renowned framework of Technology Acceptance model (TAM), Unified Theory of Acceptance and use of Technology (UTAUT) model and three other factors. Self-administered questionnaires were developed and distributed around Klang Valley, Malaysia targeting Malaysian at the age of 18-60. This study reflects the perception of users and non-users of mobile banking services. Out of the 400 questionnaires distributed, only 377 useable questionnaires were being used for analysis purpose. The analyses were done using the SPSS and SmartPLS software and results show out of the six independent variables, five factors, perceived credibility, perceived ease of use, perceived usefulness, perceived enjoyment and social influence were found to have a positive relationship with the intention to adopt mobile banking while perceived risks were found to be negatively associated with the intention to adopt mobile banking services. The results of this research are believed to be able to provide useful insights and important implication to financial institutions, academician and the society as a whole in yielding higher adoption level of mobile banking. Several implications and recommendations are being discussed in Chapter 5.